An Analytical Study Of The Reality Of Educational And Psychological Guidance In Distinguished Schools In Babylon Governorate From The Student's Point Of View - Marwah Ali Hamzah, (Musamus Journal of Physical Education and Sport (MJPES), 2025)
Purpose of this paper is to develop a questionnaire to identify  reality of psychological and educational counseling in schools for gifted students in Babylon Governorate, and to identify  reality of psychological and educational counseling in these schools from  students' perspective. The researcher adopted  descriptive-analytical method, as it is suitable for  purposes of this study.  research community was defined as students of  Gifted Students School in Babylon Governorate for  academic year 2024-2025, totaling (751) students. A random sample of (170) students, representing 22.636% of  research community, was selected by lottery. The researcher administered  questionnaire in its final form, consisting of (25) paragraphs, to 170 students in study sample between December 20, 2024, and December 25, 2024. Questionnaires were then collected, and  data from  sample's responses was compiled and statistically analyzed.  most important conclusions reached were that  psychological counselors in  Gifted Students Schools in Babylon possess strong interpersonal skills and  ability to build positive relationships with colleagues and students. Furthermore, psychological counselors in Gifted Students Schools in Babylon demonstrate high professional competence and possess  interpersonal skills that qualify them to be distinguished counselors. There is also a high demand among students for consultations with  psychological counselors at school.